The Effect of Using Digital Storytelling on Students’ Reading Comprehension and Listening Comprehension - Hamdy, Muhammad Fajri (Journal of English and Arabic Language Teaching, 2017)
The purpose of this study was to find out the effect of using digital storytelling strategy on students' reading comprehension and listening comprehension. The design of this study was Quasi-Experimental with pretest and post-test. Thus, two classrooms containing the total of 60 students of level II at Language Development Center of UIN Suska Riau were selected as the sample based on their similar characteristics and were assigned into an experimental and a control group. In collecting the data, reading and listening   tests   as   well   as   observations   were   utilized   to   assess   participants’ comprehension abilities prior to and after the treatment. In analyzing the data, the t-tests (paired sample, and independent sample) were run in SPSS. In addition, Cohen D formula was applied to determine the effect size. The results showed that there were no significant differences (p > 0.05) between the means of the pretests scores, and there were significant differences (p < 0.05) between the means of both groups post-tests scores,  reading  comprehension  (p=0.02),  and  listening  comprehension  (p=0.04).  In other words, the students’ comprehension levels were similar prior to the treatment, and the students of the experimental group outperformed the control group after the treatment. In addition, the values of the effect size obtained, reading (0.5), and listening (0.5), were categorized into the moderate effect size. Thus it was inferred that the use of digital storytelling had a significant effect on students’ reading and listening comprehension at Language Development Center of UIN Suska Riau.